In vitro Evaluation of the Antibacterial Activity of the Combination of Avibactam and β-Lactams Against Highly Virulent Carbapenem-Resistant Klebsiella pneumoniae - Chang J; Peng X; Wang X; Zhang Z (Infection and Drug Resistance)
Jianliang Chang,1,2 Xiaocui Peng,1,2 Xue Wang,1,2 Zhihua Zhang2 1Graduate School of Hebei North University, Zhangjiakou, Hebei, 075000, People’s Republic of China; 2Respiratory and Critical Care Medicine Department, The First Affiliated Hospital of Hebei North University, Zhangjiakou, Hebei, 075000, People’s Republic of ChinaCorrespondence: Zhihua Zhang, Respiratory and Critical Care Medicine Department, The First Affiliated Hospital of Hebei North University, Zhangjiakou, Hebei, 075000, People’s Republic of China, Email 3167713449@qq.comPurpose: To study the resistance of carbapenem-resistant Klebsiella pneumoniae to β-lactams combined with avibactam, as well as the distribution of resistance and virulence genes, and to analyze the clinical characteristics of infected patients.Methods: Antibiotic susceptibility was examined using the trace broth dilution method. Carbapenem-resistance genes, porins, and virulence genes were identified using PCR. Strain adhesion was assessed through wire-drawing experiments, and clinical data from infected patients were collected.Results: Among 80 CRKP strains, 93.8% harboured blaKPC-2, and 1.3% harboured both blaKPC-2 and blaNDM. Some strains lacked OMPK35 (6.2%) and OMPK36 (10%). Virulence genes ycfM, entB, fimH, irp-1, and prmpA2 were prevalent. The combination of carbapenems, cephalosporins, and aztreonam with avibactam significantly lowered MIC values compared to single drugs (P< 0.01). Significant differences in MIC were noted between low and high avibactam concentrations (P< 0.05).Conclusion: CRKP harbouring virulence genes poses significant risks. Combining carbapenems, cephalosporins, and avibactam enhances antibacterial activity against CRKP.Keywords: blaKPC-2 gene, blaNDM gene, virulence gene, minimum inhibitory concentration, antibacterial activity, infection